IMPACT OF METRICAL PROSODY ON PERFORMANCES - Adi Putra Wijaya; Sri Minda Murni (State University of Medan, 2015)
This thesis is about testing Frederick Turner and Ernst Pöppel’s claim that suggestmetrical poem tends to measure three seconds in terms of psychological limitwhen it is performed aloud. The objective of the study is to present metricalpoems as the new data to test their claim by using corpus analysis. Hereby, theresearcher uses publicly available 28 read-aloud poems from poetryoutloud.orgby using Praat to find the duration of each metrical line. The findings indicate thatthere are 18 English metrical poems with 314 lines in total, supported by metricaltree analysis, meanwhile there are 10 poems which are free verse and found that1) most lines have iamb feet, 2) 10 of the metrical pattern of the poems are iambicpentameter, whereas others are in diverse meter, 3) there is no psychological limiton the duration of metrical lines in performance as the researcher only founds62.73% that fit to the 3 seconds of temporal window based on the analysis in thecorpus of 314 metrical lines. This study has shown what Frederick Turner andErnst Pöppel claim is not methodologically proven.